1997
DOI: 10.1016/s1074-7613(00)80402-1
|View full text |Cite
|
Sign up to set email alerts
|

MyD88: An Adapter That Recruits IRAK to the IL-1 Receptor Complex

Abstract: IL-1 is a proinflammatory cytokine that signals through a receptor complex of two different transmembrane chains to generate multiple cellular responses, including activation of the transcription factor NF-kappaB. Here we show that MyD88, a previously described protein of unknown function, is recruited to the IL-1 receptor complex following IL-1 stimulation. MyD88 binds to both IRAK (IL-1 receptor-associated kinase) and the heterocomplex (the signaling complex) of the two receptor chains and thereby mediates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
739
5
10

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,028 publications
(778 citation statements)
references
References 71 publications
24
739
5
10
Order By: Relevance
“…Whether it functions like TRADD is not known negative which blocks NF-kB activation by IL-1, but not by TNF. Both the N-and C-terminal fragments of MyD88 were observed to interact with IRAK (Wesche et al, 1997a). Formation of MyD88 homodimers, mediated via the death domain, was observed as well.…”
Section: Egr-1 ±Modulation Of Lineage Speci®c DI Erentiation and Rolementioning
confidence: 84%
See 1 more Smart Citation
“…Whether it functions like TRADD is not known negative which blocks NF-kB activation by IL-1, but not by TNF. Both the N-and C-terminal fragments of MyD88 were observed to interact with IRAK (Wesche et al, 1997a). Formation of MyD88 homodimers, mediated via the death domain, was observed as well.…”
Section: Egr-1 ±Modulation Of Lineage Speci®c DI Erentiation and Rolementioning
confidence: 84%
“…Several reports in the last year have identi®ed MyD88 as an adapter that recruits IRAK to the IL-1 receptor complex Wesche et al, 1997a;Muzio et al, 1997) (Figure 3). It was shown that following IL-1 stimulation MyD88 binds to both IRAK and the IL-1R/IL-1AcP receptor complex, thereby linking IRAK to the receptor.…”
Section: Egr-1 ±Modulation Of Lineage Speci®c DI Erentiation and Rolementioning
confidence: 99%
“…All TLRs except TLR3 and TLR4 have been shown to require MyD88 for effective downstream signaling, dividing the TLR family between MyD88-dependent and MyD88-independent members [15]. In the case of pathogenic invading, MyD88 was up-regulated to enhance the activation of downstream transcription factors, such as NF-kB and AP-1 [16]. In the MyD88-independent TLR signaling pathway, TLR3 induce the activation of the IFN-b promoter, a function unimpaired by the knockdown of MyD88 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, we found two novel truncated forms of Myd88 lacking DD domain, CgMyD88-T1 and CgMyD88-T2. Both CgMyD88Ts contain the conserved TIR domain, which has previously been proved to be required for mediating TLR/MyD88 heterodimerization to activate the followed signaling transduction [19].…”
Section: Discussionmentioning
confidence: 99%